NEW REMAINS OF BRACHYPOTHERIUM FATEHJANGENSE FROM LOWER SIWALIK, HILLS, PUNJAB, PAKISTAN - A. M. Khan; A. Habib; M. A. Khan; M. Ali; M. Akhtar (Journal of Animal and Plant Sciences, 2010)
The new unpublished remains of Brachypotherium are described. The material collected from the Chinji Formation includes four upper premolars; two upper molars; one lower premolar and a fourth lower milk molar. On the basis of brachydont teeth, the large size, wide and evenly flat or slightly concave ectoloph surface behind the rather insignificant paracone rib in the lower milk molar, persistence of internal cingula on its upper cheek teeth and of the external cingula on its upper and lower molars, the specimens are assigned to Brachypotherium fatehjangense.
Keywords: Brachypotherium fatehjangense; Chinji Formation; Lower Siwaliks